2019
DOI: 10.1002/adem.201900752
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Evolution of Strength and Microstructure of High‐Entropy Alloy CoCrFeNiMn after High‐Pressure Torsion at 300 and 77 K

Abstract: Ultrafine and nanocrystalline states of equiatomic face‐centered cubic (fcc) high‐entropy alloy (HEA) CoCrFeNiMn (“Cantor” alloy) are achieved by high‐pressure torsion (HPT) at 300 K (room temperature, RT) and 77 K (cryo). Although the hardness after RT‐HPT reaches exceptionally high values, those from cryo‐HPT are distinctly lower, at least when the torsional strain lies beyond γ = 25. The values are stable even during long‐time storage at ambient temperature. A similar paradoxal result is reflected by torque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 47 publications
7
21
0
Order By: Relevance
“…The spotty TEM diffraction pattern for HPT at LNT in comparison to that at RT [4] indicates that with decreasing temperature deformation becomes more heterogeneous. It should be mentioned that despite of differences in the production of the starting HEA material resulting in different grain sizes and probably slightly different textures, and differences in HPT parameters (sample size, hydrostatic pressure, rotation speed), the steady-state crystallite sizes and dislocation and twin densities as well as microhardness values reported agree quite well with those of the present study, both for HPT at RT [23,24] and LNT [23]. An exception are the results given in [25], where evidently the steady-state has not been reached.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The spotty TEM diffraction pattern for HPT at LNT in comparison to that at RT [4] indicates that with decreasing temperature deformation becomes more heterogeneous. It should be mentioned that despite of differences in the production of the starting HEA material resulting in different grain sizes and probably slightly different textures, and differences in HPT parameters (sample size, hydrostatic pressure, rotation speed), the steady-state crystallite sizes and dislocation and twin densities as well as microhardness values reported agree quite well with those of the present study, both for HPT at RT [23,24] and LNT [23]. An exception are the results given in [25], where evidently the steady-state has not been reached.…”
Section: Resultssupporting
confidence: 89%
“…Comparing these values with σ max it is concluded that the yield stress of the nanocrystalline Cantor alloy at RT is predominantly determined by dislocation-dislocation interaction. A similar conclusion has been drawn by Podolskiy et al [23] and Heczel et al [24]. Moreover, Podolskiy et al [23] argued that the smaller strength at cryogenic HPT processing can be understood as an indirect consequence of the shear-induced FCC to HCP martensitic phase transformation.…”
Section: Strength Developmentsupporting
confidence: 67%
See 3 more Smart Citations